COMPETITIVENESS ANALYSIS OF ROBUSTA COFFEE IN PAMIJAHAN DISTRICT, BOGOR REGENCY WEST JAVA - Muhammad Rizal Amri; Nia Rosiana (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2022)
One of the plantation commodities, which is Indonesia's leading export commodity is coffee. Increasing competition among competitors has an impact on the level of coffee competitiveness. The existence of government policies related to the elimination of Registered Coffee Exporters (ETK) need to be studied because it will impact coffee competitiveness. This study aims to analyze comparative and competitive advantages and the impact of government policies on the competitiveness of robusta coffee farming in Pamijahan District, Bogor Regency. The purposive sampling method was used to collect data through questionnaires to robusta coffee farmers. Competitiveness analysis uses the Policy Analysis Matrix (PAM) method. The results showed that robusta coffee farming in Pamijahan District had a comparative advantage, namely DRC obtained 0.05 and competitive advantage with PCR value obtained 0.05. The overall impact of the ETK elimination policy has a positive impact on farmers on inputs, outputs, and inputs-outputs.